2009
DOI: 10.1021/cg800592y
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Anion and Solvent in the Self-Assembly of Silver(I) Complexes Containing 2,3-Diphenylquinoxaline

Abstract: A series of Ag(I) complexes with zero-, one-and two-dimensional structures have been successfully prepared by the reactions of 2,3-diphenylquinoxaline, L, with corresponding Ag(I) salts in various solvents, which were characterized by elemental analysis, IR spectra and single crystal X-ray diffraction. Complexes of the type [Ag(L) 2 ](X) (X ) ClO 4 , 1; X ) PF 6 , 2; and X ) SbF 6 , 3) are monomeric, while the complexes {5CH 2 Cl 2 , show 1-D polymeric infinite chains. The ClO 4 anions in complex 6 interact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…The nitrates involved in the metal bonding in these complexes show three variations: the nitrate may bind one oxygen to one silver [8], two oxygen to one silver [9,13], or two oxygen on one nitrate group may bridge two silvers on separate molecules [7]. The silver geometry is either linear or bent with the perturbation to non-linear geometries caused by the cation-anion interaction.…”
Section: 2mentioning
confidence: 99%
See 3 more Smart Citations
“…The nitrates involved in the metal bonding in these complexes show three variations: the nitrate may bind one oxygen to one silver [8], two oxygen to one silver [9,13], or two oxygen on one nitrate group may bridge two silvers on separate molecules [7]. The silver geometry is either linear or bent with the perturbation to non-linear geometries caused by the cation-anion interaction.…”
Section: 2mentioning
confidence: 99%
“…Preliminary observations have shown that weakly coordinating anions such as tend to be located near the silver [6,10]. However, several structures have seen nitrate-silver interactions that lead to: monodentate O-Ag bonding [8]; bidentate nonbridging O-Ag bonding [9,13]; and bidentate bridging bonding [7]. In Ag(1) 2 NO 3 , one nitrito group oxygen is within bonding distance to the silver at a distance of 2.461 (5) Å with the other at a distance of over 3 Å.…”
Section: Nitrate Coordination To Silvermentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] This ligand can coordinate to the metal centers through their quinoxailne nitrogen atoms and interact with each other through p-p stacking and hydrogen bonds which are important for molecular recognition and constructing supramolecular arrays. In our previous report, 9 we have found that metal-to-ligand molar ratio and nature of the solvents involved in the reactions play important roles in determining the structural type of the Ag(I)-L complexes containing coordinating or non-coordinating anion. For complexes with non-coordinating anions, coordinated or packed solvent molecules show the polymeric structures, while those without solvent molecule are mononuclear.…”
Section: Introductionmentioning
confidence: 99%